2006
DOI: 10.1080/03079450601028829
|View full text |Cite
|
Sign up to set email alerts
|

The feathering gene is linked to degranulation and oxidative burst not cytokine/chemokine mRNA expression levels orSalmonella enteritidisorgan invasion in broilers

Abstract: In the past, we showed differences in heterophil function between parental broilers (A [fast feathering]/B [slow feathering]) and their F1 reciprocal crosses (D [fast feathering]/C [slow feathering]). In the present study, we evaluated the linkage of the feathering gene to heterophil function, pro-inflammatory cytokine/ chemokine mRNA expression levels, and resistance to Salmonella enteritidis organ invasion. Heterophils were isolated from 2-day-old chickens (C and D) separated into males and females*slow male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Redmond and colleagues proved heterophils from commercially selected and non-selected genetic lines expressed cytokines differently in vitro exposure to Salmonella enteritidis, where functional phenotypes of phagocytosis and bacterial killing varied depending on the breed or cross of chicken and the SLC11A1 gene was associated with phagocytosis of Salmonella enteritidis [22]. Swaggerty demonstrated genes associated with fast and slow feathering located on the Z sex chromosome were associated with the biochemical killing mechanism of degranulation and oxidative burst of heterophil in avian species [24]. This study found the phagocytosis and oxidative burst of heterophils isolated from selection lines performed more powerfully compared to the non-selection line, indicating heterophil function related genes were selected under the H/L ratio selection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Redmond and colleagues proved heterophils from commercially selected and non-selected genetic lines expressed cytokines differently in vitro exposure to Salmonella enteritidis, where functional phenotypes of phagocytosis and bacterial killing varied depending on the breed or cross of chicken and the SLC11A1 gene was associated with phagocytosis of Salmonella enteritidis [22]. Swaggerty demonstrated genes associated with fast and slow feathering located on the Z sex chromosome were associated with the biochemical killing mechanism of degranulation and oxidative burst of heterophil in avian species [24]. This study found the phagocytosis and oxidative burst of heterophils isolated from selection lines performed more powerfully compared to the non-selection line, indicating heterophil function related genes were selected under the H/L ratio selection pressure.…”
Section: Discussionmentioning
confidence: 99%